The Phenomenon of Gene Rearrangement is Frequently Associated with TP53 Mutations and Poor Disease-Free Survival in Hepatocellular Carcinoma - He F; Song K; Guan G; Huo J; Xin Y; Li T; Liu C; Zhu Q; Fan N; Guo Y; Wu L (Dove Medical Press, 2021)
Fu He,1,2 Kangjian Song,1,2 Ge Guan,3 Junyu Huo,1,2 Yang Xin,1 Tianxiang Li,3 Chao Liu,1 Qingwei Zhu,1,2 Ning Fan,1 Yuan Guo,1 Liqun Wu1 1Liver Disease Center, The Affiliated Hospital of Qingdao University, Qingdao, 266003, Shandong, People’s Republic of China; 2Department of Clinical Medicine, Qingdao University, Qingdao, 266071, Shandong, People’s Republic of China; 3Organ Transplant Center, The Affiliated Hospital of Qingdao University, Qingdao, 266003, Shandong, People’s Republic of ChinaCorrespondence: Liqun WuLiver Disease Center, The Affiliated Hospital of Qingdao University, No. 59 Haier Road, Qingdao, 266003, Shandong Province, People’s Republic of ChinaTel +86 18661809789Email wulq5810@126.comPurpose: Gene rearrangements (GRs) have been reported to be related to adverse prognosis in some tumours, but the relationship in hepatocellular carcinoma (HCC) remains less studied. The objective of our study was to explore the clinicopathological characteristics and prognosis of HCC patients (HCCs) with GRs (GR-HCCs).Patients and Methods: This retrospective study included 297 HCCs who underwent hepatectomy and had their tumours sequenced by next-generation sequencing. Categorical variables between groups were compared by the chi-square test. The impact of variables on disease-free survival (DFS) and survival after relapse (SAR) was analysed by the Kaplan–Meier method and Cox regression.Results: We observed four repetitive GR events in 297 HCCs: BRD9/TERT, ARID2/intergenic, CDKN2A/intergenic and OBSCN truncation. GR-HCCs frequently presented with low tumour differentiation, tumour necrosis, microvascular invasion, elevated AFP and gene mutations (TP53, NTRK3 and BRD9). The 1-, 2-, and 3-year cumulative DFS rates in GR-HCCs were 45.1%, 31.9%, 31.9%, respectively, which were significantly lower than those of GR-negative HCCs (NGR-HCCs) (72.5%, 57.9%, and 49.0%, respectively; P = 0.001). GR was identified as an independent risk factor for inferior DFS in HCCs (HR = 1.980, 95% CI = 1.246– 3.147; P = 0.004). However, there was no significant difference in SAR between GR-HCCs and NGR-HCCs receiving targeted therapy or immunotherapy.Conclusion: GR is frequently associated with TP53 mutations and significantly affects DFS following radical resection for HCC. We recommend that GR-HCCs should be closely followed up as a high-risk group for postoperative recurrence.Keywords: hepatocellular carcinoma, gene rearrangement, next-generation sequencing, prognosis, risk factors